2013
DOI: 10.1111/vco.12043
|View full text |Cite
|
Sign up to set email alerts
|

Flow‐cytometric detection of phenotypic aberrancies in canine small clear cell lymphoma

Abstract: Histopathology and immunohistochemistry are mandatory to solve the differential between canine low-grade lymphoma and reactive hyperplasia. However, clinicians and owners often show reluctance toward these invasive tests. However, molecular biology techniques are still not sensitive and specific enough to be regarded as a reliable tool for final diagnosis. In humans, flow cytometry (FC) allows a definitive diagnosis of T-cell lymphoma based on high prevalence of antigen aberrancies. We describe here the immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
53
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(69 citation statements)
references
References 31 publications
12
53
1
3
Order By: Relevance
“…The existence of a CD45‐negative, small clear cell/T‐zone distinct lymphoma subtype showing an indolent clinical course may be presumed in dogs . This study retrospectively describes the clinical presentation and outcome of a case series of dogs affected by this particular lymphoma subtype.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The existence of a CD45‐negative, small clear cell/T‐zone distinct lymphoma subtype showing an indolent clinical course may be presumed in dogs . This study retrospectively describes the clinical presentation and outcome of a case series of dogs affected by this particular lymphoma subtype.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, this study highlighted that lymphomas with cytological small clear cell appearance may be considered suggestive, although not conclusive, of T‐cell phenotype and representative of T‐zone lymphoma (TZL). More recently, our research group highlighted a high prevalence of phenotypic aberrancies in canine small clear cell lymphoma, mostly a lack of CD45 expression, which accounted for >95% of the cases . At the same time, another study demonstrated that 100% of canine CD45‐negative T‐cell neoplasia were histologically defined as TZL .…”
Section: Introductionmentioning
confidence: 86%
“…However, TZL is unique among canine lymphoma through its CD45− and CD21+ phenotype [66,69]. The expression of CD4 and CD8 is variable as single positive, dual positive, and dual negative variants have been described [66,69,73]. …”
Section: T-cell Neoplasmsmentioning
confidence: 99%
“…Because no definitive rules on the best way to report fluorescence intensity of antigens in FC reports of canine hematopoietic neoplasms have been generated to date, some recommendations are proposed: (1) antigen expression may be preferentially expressed as dim or bright and data on distribution of the antigen (homogeneous vs. heterogeneous) should be provided only if useful to discriminate between normal and neoplastic populations, to define subtype, to track infiltration/residual disease of neoplastic cells (when quantitative aberrant patterns are present) or to define prognosis; (2) when this quantitation is reported, the definition of neoplastic cells as dim or bright should be well standardized for each antigen and consistent with methods from published references; 3) in the absence of specific published references, the criteria used for defining quantitative antigen expression (dim vs. bright) could be provided in supplementary notes, together with the putative biological meaning; (4) when possible, quantitative expression of antigens should be compared with the closest normal hemic population; (5) quantitative findings that are irrelevant to clinical importance (i.e., not involving staging, prognosis, minimal residual disease, etc.) should be avoided; (6) data regarding in-progress studies should be omitted from the diagnostic report until they complete the peer-review and publication process.…”
Section: Minor Issuesmentioning
confidence: 99%
“…Flow cytometry (FC) is increasingly being used in veterinary clinical pathology laboratories owing to the increasing number of FC facilities, greater availability of specific antibodies labeled with different fluorochromes, and the rapidity with which results can be generated. Immunophenotyping hematopoietic neoplasms is one of the most important applications of FC in veterinary clinical pathology diagnostics since this method rapidly provides useful information on the lineage of neoplastic cells, identifies some specific neoplastic subtypes (T zone lymphomas, chronic lymphocytic leukemia) (1)(2)(3)(4), accurately defines stage (5) and, in some cases, can detect minimal residual disease (6).…”
mentioning
confidence: 99%